Missing the marks? Dispersion in corporate bond valuations across mutual funds - Gjergji Cici; Scott Gibson; John J. Merrick (University of Cologne, Centre for Financial Research (CFR), 2010)
We study the dispersion of month-end valuations placed on identical corporate bonds by different mutual funds. Such dispersion is related to bond-specific characteristics associated with liquidity and market volatility. TRACE may have contributed to the general decline in dispersion over our sample period, though other factors most likely played roles. Further tests reveal marking patterns to be consistent with returns smoothing behavior by managers. Funds with ambiguous marking policies and those holding 'hard-to-mark' bonds appear more prone to smooth reported returns. From a regulatory perspective, we see little downside to requiring funds to explicitly state their marking standards.
Keywords: 330; Rentenfonds; Industrieobligation; Kapitalertrag; Bewertung; Portfolio-Management; Benchmarking; Schätzung; USA